Constructing identities – the exhibition as a form to present the Peranakan within a museum context in Singapore - Tan, Luke Mathew Dong Sheng (Nanyang Technological University, 2022)
This thesis explores the role of the exhibition in constructing Peranakan identity within the Singapore context. The analysis centres on the physical aspects of the respective museum's permanent exhibition and focuses on (1) the use of the physical space/architecture and (2) use of exhibited material culture to manifest the curatorial intention and/or exhibition's narrative (which inherently determines and shapes audience's perception of the Peranakan identity). Interviews were conducted with three individuals who operate within the museum context to supplement existing material and research as well as to generate contemporary insights into the subject matter.